Middle-distance running acutely influences the concentration and composition of serum bile acids: Potential implications for cancer risk? - Danese, Elisa (Oncotarget, 2017)
BACKGROUND: This study was aimed to investigate the acute effect of medium-distance running on bile acids concentration and composition, in order to verify whether the positive impact of physical exercise on cancer risk may also be mediated by variation of bile acids concentration and composition in serum. METHODS: The concentration and composition of serum bile acids was analyzed in 30 middle-aged and healthy recreational athletes with a reference liquid chromatography-mass spectrometry technique, immediately before and shortly after the end of the running trial. The concentration of bile acids after the run was adjusted for plasma volume change. RESULTS: All athletes successfully completed the trial. After correction of values for the individual plasma volume change calculated after the run, the serum concentration of total bile acids was found to be significantly reduced by approximately 46%. A statistically significant decrease was observed for cholic, deoxycholic, chenodeoxycholic, ursodeoxycholic, glycoursodeoxycholic and hyodeoxycholic acids, whereas the concentration of the remaining compounds remained unvaried after the run. A considerable variation of bile acids profile was also observed. No significant association was found between running performance and variation of bile acids concentrations. CONCLUSION: These results show that middle distance running acutely decreases the concentration of total bile acids in serum, especially that of the more mutagenic and carcinogenic compounds, so providing an intriguing support to the favorable effects of physical exercise for lowering the risk of many gastrointestinal cancers.